The poverty of forestry policy: double standards on an uneven playing field - Larson, A.M.; Ribot, J.C. (Springer, 2007)
Can policies designed to maximize exploitation by elites benefit the people who live in forests? Forestry policy throughout the developing world originates from European ‘‘scientific’’ forestry traditions exported during the colonial period. These policies were implemented by foreign and local elite whose interest was to maximize and extract profit. In spite of reforms since the end of the colonial period, policies on the environment usually remain biased against rural communities. Even when more recent policies are fair, the rural poor face severe biases in implementation. In addition, they must compete on an uneven playing field of ethnic and other social inequities and economic hurdles. This article examines how forestry policy and implementation maintain double standards on this uneven playing field in a manner that permanently excludes the rural poor from the natural wealth around them—producing poverty in the process. Change that would support poverty alleviation for forest-based communities requires a radical rethinking of forest policy so as to counterbalance widespread regressive policies and structural asymmetries.